Polyclonal IgY supplementation at birth did not affect preweaned dairy calf health - De La Cuadra Rojas, Luisa Fernanda, author; Raabis, Sarah, advisor; Cramer, Catie, committee member; Applegate, Tanya, committee member (Colorado State University. Libraries, 2025)
Diarrhea in dairy calves has a significant impact on farm economics, primarily due to weight loss, increased labor for farm staff, and treatment costs. Antimicrobials are commonly used for the prevention and treatment of this disease, but their overuse contributes to antimicrobial resistance (AMR), making calves key reservoirs of resistance genes. Alternatives to the use of antimicrobials have been widely researched, and immunoglobulin Y (IgY) is one of them. This is an immunotherapy that utilizes IgY extracted from egg yolk to reduce pathogen colonization, with promising results in the treatment of calf diarrhea. IgY can be either monoclonal or polyclonal. Monoclonal IgY products target single pathogens, however, they may be less effective in neonatal calves exposed to multiple enteric pathogens simultaneously. Gastrointestinal infections can also predispose calves to respiratory illnesses, such as bovine respiratory disease (BRD), thereby compounding health and economic burdens, including increased use of antimicrobials. This study evaluated the effect of a commercial polyclonal IgY supplement on pre-weaned calf health. A randomized controlled trial was conducted between December 2023 and March 2024 on a commercial dairy farm. Sample size (n=80) was calculated to detect a 20% difference in days with diarrhea between groups (1-β=0.8; α=0.05). A total of 187 calves were enrolled and assigned to a treatment (IGY; n=91) or control group (CON; n=96). Health indicators included fecal score (FS), body weight, fecal shedding of pathogens (Salmonella culture and qPCR for BCoV, BRV, and Cryptosporidium parvum) were collected. Descriptive statistics were performed to summarize data. Chi-square was applied to establish statistical significance between groups for different outcomes (BRD prevalence, pathogen shedding for Salmonella, BCoV, BRV, and C. parvum. Multivariable models assessed the effect of IgY supplementation on diarrhea (FS ≥2, days 1-14), pathogen shedding, and average daily gain (ADG). A total of 187 calves were enrolled in the study, 91 animals assigned to the treatment group (IGY) and 96 to the control group (CON). Farms staff administered the supplement within 12 hours of birth to 66% of the calves in the IGY group. The mean ADG between groups was not statistically significant (p = 0.698, 0.81 kg +- 0.05;88). The IGY group was not significantly associated with the odds of having BRD (OR = 0.76, 95% CI [0.53-1.08], P = 0.1240). The treatment group was not associated with the likelihood of having at least one day with an FS ≥2 (OR = 1.05, 95% CI [0.76-1.45]) or FS ≥3 (OR = 0.67, 95% CI [0.36-1.2], p = 0.176). No statistically significant difference in Salmonella (p = 0.25) or Cryptosporidium parvum (p = 0.14) shedding. There were also no significant differences detected in the odds of pathogen shedding (P> 0.2), BCoV (OR: 2.43, CI: 0.7-8.88), and BRV (OR:1.08, CI: 0.30-3.85). Mortality remained low across groups, and farm treatment for diarrheic patients showed no statistically significant difference between groups for both parameters. In conclusion, a single dose of a mixture supplement with IgY administered within the first 12 hours of birth was not associated with BRD presentation, fecal score, prevalence of diarrhea, pathogen shedding, improvement of ADG, decreased mortality or treatments for diarrhea at the farm either during the first 14 days or during the first 60 days of life.
Keywords: dairy; IgY; polyclonal; diarrhea; calf; neonate